2009
DOI: 10.1503/cmaj.081968
|View full text |Cite
|
Sign up to set email alerts
|

Sudden loss of vision: Purtscher retinopathy in multiple myeloma

Abstract: A 53-year-old man presented with acute, severe loss of vision in both eyes. Three days earlier, he had noticed a painless deterioration of his vision, which had progressed until he could no longer read a newspaper using either eye. On examination, the patient's best corrected visual acuity was 20/100 using both eyes. He had full visual fields by confrontation and the motility of extraocular muscles was normal. No afferent pupillary defect was evident. Examination of the posterior segment showed bilateral edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Other pathogenic processes that may be involved include capillary endothelial damage (supported by late leakage in IVFA 16 ), sudden increase of intracranial pressure (causing precapillary occlusion in lamina crivosa 43,46 ), sudden expansion of retinal veins, 7 or hyperviscosity (such as in multiple myeloma 47 ). A recent study used computer dynamic flow simulations and suggested an additional mechanism: an inner layer retinal posterior pole rheological event that results in vascular endothelial dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathogenic processes that may be involved include capillary endothelial damage (supported by late leakage in IVFA 16 ), sudden increase of intracranial pressure (causing precapillary occlusion in lamina crivosa 43,46 ), sudden expansion of retinal veins, 7 or hyperviscosity (such as in multiple myeloma 47 ). A recent study used computer dynamic flow simulations and suggested an additional mechanism: an inner layer retinal posterior pole rheological event that results in vascular endothelial dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, capillary endothelial damage and hyperviscosity have also been suggested to play roles in Purtscher-like retinopathy. 11,12 Since vasculitis-associated endothelial damage is not uncommon in SLE, which can result in thrombosis, we speculate that in SLE several mechanisms are involved, including precapillary arteriole occlusion followed by altered retinal microvascular permeability. Our observation suggests that SLE-associated antiphospholipid syndrome (APS) is not likely a main mechanism in Purtscher-like retinopathy, although APS can lead to thrombosis.…”
Section: Purtscher Retinopathy Was Initially Described Inmentioning
confidence: 96%
“…Lupus nephritis was defined as the presence of proteinuria or cellular casts containing red blood cells and hemoglobin. Disease activity was measured using the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) developed in 2000, categorized as no activity (SLEDAI ¼ 0), mild activity (SLEDAI ¼ 1-5), moderate activity (SLEDAI ¼ 6-10), high activity (SLEDAI ¼ [11][12][13][14][15][16][17][18][19], and very high activity (SLEDAI > _20). [7][8][9] To evaluate the correlation between Purtscher-like retinopathy and other clinical characteristics of SLE, particularly CNS lupus, 240 control patients were randomly selected from all SLE patients without Purtscher-like retinopathy admitted during the study period, stratified by sex and 2 age categories (<18 years and > _18 years).…”
Section: This Study Was An Observational Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled complement activation has been proposed to play a major role in the pathogenesis of Purtscher-like retinopathy by mechanisms involving endothelial damage and activation of the clotting cascade [ 5 , 6 , 13 , 14 ] and development of leukocyte and platelet aggregates [ 1 , 4 ]. Other proposed mechanisms include intravascular volume surge such as in sudden expansion of retinal veins [ 1 ], hyperviscosity [ 15 ], intracephalic shock waves such as in sudden increase in intracranial pressure with resulting precapillary occlusion at the level of the lamina cribrosa [ 16 ], capillary endothelial damage [ 17 ] and vascular endothelial dysregulation and ensuing endothelin-induced vasculopathy [ 16 ]. Associated systemic entities include acute pancreatitis [ 18 25 ], pancreatic adenocarcinoma [ 26 ], systemic lupus erythematosus [ 27 ], renal failure [ 28 , 29 ], amniotic fluid embolization [ 12 ], thrombotic thrombocytopenic purpura [ 30 33 ], hemolytic uremic syndrome (HUS) [ 31 , 34 ] and cryoglobulinemia [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%